The contribution of the Magisterium on the subject of human artificial insemination - Leuzzi, Lorenzo (Medicina e Morale, 2024)
The need for knowledge of the Magisterium's thinking on the subject of human artificial insemination has been felt in many quarters. The present work seeks to respond to this need by presenting and, at the same time, structuring the interventions themselves so as to guide research and in-depth study. These interventions by the Magisterium can be divided into two broad sections: 'specific' interventions and 'indirect' interventions. This subdivision is not accidental. It is useful because it allows a mutual enrichment of the interventions themselves in order not only to their true and authentic interpretation, but also to the understanding of their theological and 'prophetic' richness.